Role of Lipid Peroxidation in Cellular Responses to D, L-Sulforaphane, A Promising Cancer Chemopreventive Agent - Sharma, Rajendra (2010)
D, L-Sulforaphane (SFN), a synthetic analogue of broccoli-derived L-isomer, is a highly promising cancer chemopreventive agent substantiated by inhibition of chemically-induced cancer in rodents and prevention of cancer development and distant site metastasis in transgenic mouse models of cancer. SFN is also known to inhibit growth of human cancer cells in association with cell cycle arrest and reactive oxygen species-dependent apoptosis, but the mechanism of these cellular responses to SFN exposure is not fully understood. Because 4-hydroxynonenal (4-HNE), a product of lipid peroxidation (LPO), the formation of which is regulated by hGSTA1-1, assumes a pivotal role in oxidative stress-induced signal transduction, the present study investigated its contribution in growth arrest and apoptosis induction by SFN using HL60 and K562 human leukemic cell lines as model. The SFN-induced formation of 4-HNE was suppressed in hGSTA1-1 over expressing cells, which also acquired resistance to SFN-induced cytotoxicity, cell cycle arrest, and apoptosis. While resistance to SFN-induced cell cycle arrest by ectopic expression of hGSTA1-1 was associated with changes in levels of G2/M regulatory proteins, resistance to apoptosis correlated with increased Bcl-xL/Bax ratio, inhibition of nuclear translocation of AIF, and attenuated cytochrome c release in cytosol. The hGSTA1-1 over expressing cells showed enhanced cytoplasmic export of Daxx, nuclear accumulation of transcription factors Nrf2 and HSF1, and up regulation of their respective client proteins, γ-GCS and HSP70. These findings not only reveal a central role of 4-HNE in cellular responses to SFN but also reaffirm that 4-HNE contributes to oxidative stress mediated signaling.